2016
DOI: 10.5740/jaoacint.15-0289
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of β-Glucan in Mushrooms and Mycelial Products

Abstract: A robust and reliable method has been developed for the measurement of β-glucan in mushroom and mycelial products. Total glucan (plus free glucose and glucose from sucrose) was measured using controlled acid hydrolysis with H2SO4 and the glucose released specifically was measured using glucose oxidase/peroxidase reagent. α-Glucan (starch/glycogen) plus free glucose and glucose from sucrose were specifically measured after hydrolysis of starch/glycogen to glucose with glucoamylase and sucrose to glucose plus fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 24 publications
7
78
2
Order By: Relevance
“…32.3 g per 100 g d.w., was also observed in one strain of P. ostreatus. 10 Similarly, considering two strains of P. eryngii, the β-glucan content was found to vary between 23.85 and 37.1 g per 100 g d.w. 10,17 Beside the genetic factors, the growing conditions affect the β-glucan content: substrates with a high content of polyphenolic compounds induce an increased synthesis of β-(1→3) D-glucan synthetase in their fruiting bodies. Factors such as the C/N ratio, pH of the substrate and the incubation temperature are also important and species specific.…”
Section: Composition and Nutritional Valuementioning
confidence: 97%
See 2 more Smart Citations
“…32.3 g per 100 g d.w., was also observed in one strain of P. ostreatus. 10 Similarly, considering two strains of P. eryngii, the β-glucan content was found to vary between 23.85 and 37.1 g per 100 g d.w. 10,17 Beside the genetic factors, the growing conditions affect the β-glucan content: substrates with a high content of polyphenolic compounds induce an increased synthesis of β-(1→3) D-glucan synthetase in their fruiting bodies. Factors such as the C/N ratio, pH of the substrate and the incubation temperature are also important and species specific.…”
Section: Composition and Nutritional Valuementioning
confidence: 97%
“…Hence, it has been recommended to calculate the β-glucan content as the difference between the total glucans (by measuring glucose obtained through a controlled acid hydrolysis) and the α-glucans (by measuring glucose released from α-glucans through enzymatic hydrolysis with α-amylase and amyloglucosidase). 10 Using this latter approach, a study on the intraspecific variability among 16 strains of P. ostreatus mushrooms revealed that the total glucan content varied in the range 14-25 g per 100 g d.w., with β-glucans in the range of 10.9-22.9 g per 100 g d.w. 24 A higher β-glucan content, i.e. 32.3 g per 100 g d.w., was also observed in one strain of P. ostreatus.…”
Section: Composition and Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…No. K-YBGL Megazyme International, Bray, County Wicklow, Ireland), based on the method published by McCleary and Codd [20]. Human immortalized HaCat keratinocyte cell line was obtained from CLS Cell Lines Service GmbH (Eppelheim, Germany) after a Material Transfer Agreement, and Dulbecco's modified Eagle's medium (DMEM) and fetal bovine serum (FBS) were obtained from Thermo Fisher Scientific (Waltham, MA, USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Cellular debris were removed by extensive washing with PBS. Then, the cells were treated with DMEM and 10% FBS containing glucan samples at different concentrations (10,20,50, and 100 µg mL −1 ). The cells were then incubated at 37 • C in a humidified 5% CO 2 atmosphere for 24 and 48 h. The scratch area was periodically imaged, at 0, 24, and 48 h acquired at 40× of magnification (Leica DMIL, Buccinasco (MI), Italy) in clear field.…”
Section: In Vitro Scratch Testmentioning
confidence: 99%